2020
DOI: 10.1111/jam.14812
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of rumen fermentation and microbial community through increasing dietary cation–anion difference in Chinese Holstein dairy cows under heat stress conditions

Abstract: Aims The effect of increasing dietary cation–anion difference (DCAD) on rumen fermentation and ruminal microbial community in dairy cows under heat stress (HS) conditions were evaluated. Methods and Results This study was performed as a two‐period cross‐over design during the summer season, with eight lactating dairy cows randomly distributed to either a control DCAD diet (CON: 33·5 mEq/100 g DM) or high DCAD diet (HDCAD: 50·8 mEq/100 g DM). Throughout the present study, the temperature and humidity index (THI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 61 publications
4
19
0
Order By: Relevance
“…Many studies, including our previous investigations, have verified that Bacteroidetes, Firmicutes, and Proteobacteria are primarily the three most predominant bacterial phyla existing within the rumen ecosystem despite different ages or regions of the ruminants, employing the 16S rRNA amplicon sequencing based on either DNA or RNA isolated from the rumen contents (Jami et al, 2013;Rey et al, 2014;Liu et al, 2016;Wang et al, 2016aWang et al, , 2017aWang et al, , 2020c. The current trial also showed that the ruminal microbiota at the phylum level was sequentially dominated by Firmicutes, Bacteroidetes, and Proteobacteria via the full-length 16S rRNA gene sequencing, which further confirmed the conclusions of previous studies.…”
Section: Discussionmentioning
confidence: 88%
“…Many studies, including our previous investigations, have verified that Bacteroidetes, Firmicutes, and Proteobacteria are primarily the three most predominant bacterial phyla existing within the rumen ecosystem despite different ages or regions of the ruminants, employing the 16S rRNA amplicon sequencing based on either DNA or RNA isolated from the rumen contents (Jami et al, 2013;Rey et al, 2014;Liu et al, 2016;Wang et al, 2016aWang et al, , 2017aWang et al, , 2020c. The current trial also showed that the ruminal microbiota at the phylum level was sequentially dominated by Firmicutes, Bacteroidetes, and Proteobacteria via the full-length 16S rRNA gene sequencing, which further confirmed the conclusions of previous studies.…”
Section: Discussionmentioning
confidence: 88%
“…Information on the ecology and biology of Dubosiella is scarce, and the differentiation mechanism of the above taxa among different treatments in this experiment are undefined, so further investigations are necessary (Wang et al . 2020a, 2020b). We conclude that oral administration of TL106 to mice improved gut microflora and enhanced intestinal health in mice.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment group tended to visit drinking troughs more frequently compared with the control group. Therefore, Wang et al (2020) recommended supplementation of an appropriate electrolyte dose for Bos Taurus exposed to heat stress, that enhanced milk production in the treatment group, while the fat % was decreased logically.…”
Section: Discussionmentioning
confidence: 99%
“…Abdelatty et al (2018) and Conte et al (2018) observed that the hyperthermia led to increase respiratory rate accompanied by panting that decreased the HCO 3 buffer levels in saliva and blood and contributed to an increase in incidence rate of ruminal acidosis where acetate concentrations and acetate to propionate ratios increased significantly. The threshold of heat stress in dairy cattle was reported to be above 72 temperature-humidity index (THI) (Wang et al, 2020). Recently, many management plans were set to avoid heat stress consequences that are considered one of the main climatic change's manifestations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation